Evaluating Myricetin as a CDK2 Inhibitor in Lung Cancer: In silico and in vitro Assessment of a Flavonoid-Based Small Molecule - Asiri, Abdulaziz (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Inhibiting Cyclin-Dependent Kinase 2 (CDK2) holds significant therapeutic potential for lung cancer by targeting a critical regulator of the cell cycle. CDK2 inhibition halts cancer cell proliferation, induces apoptosis, and disrupts tumor progression. Flavonoids have recognized to be exceedingly effective in treating a wide range of diseases, together with cardiovascular, immunological disorders, and cancer. Materials and Methods: This study intended to investigate the possible of flavonoid small molecules as CDK2 inhibitors. We examined the potential of the lead compound, myricetin, as a CDK2 inhibitor and its cytotoxic effects on A549 lung carcinoma cells using in silico and in vitro methods. Results: Molecular docking revealed a high binding affinity, -8.6 kcal/mol, of myricetin to CDK2, with interactions involving key amino acid residues, including hydrogen bonds with ASP86, ASP145, and ASN132, as well as various other non-covalent interactions. ADMET analysis demonstrated favourable pharmacokinetic properties of myricetin, with promising predictions for kinase inhibition, apoptosis induction, and anticancer activity. Swiss Target Prediction highlighted myricetin's potential to modulate diverse biological targets, including enzymes, kinases, and G-protein-coupled receptors. Myricetin exhibited a concentration- and time-dependent cytotoxic effect on A549 cells, with an IC50 of 93.41 µM. Cell viability decreased significantly up to 48 hr but then plateaued. Myricetin also significantly downregulated CDK2 mRNA expression and activity in a dose-dependent manner, with reductions observed across half, IC50, and double IC50 concentrations. Conclusion: These findings suggest that myricetin is a promising candidate for CDK2 inhibition and lung cancer treatment, warranting further investigation into its mechanism of action and therapeutic potential.
Keywords: CDK2 inhibition; Flavonoids; Lung cancer; Molecular docking; Myricetin